2018
DOI: 10.3390/en11040926
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Damage to Hard Brittle Shale with Stress and Hydration Coupling

Abstract: Acoustic-wave velocities of shale rocks with different coring angles were tested by an acoustic-emission experiment under different confining pressures and soaking time of drilling fluid. Effects of stress and hydration coupling on the acoustic-wave velocities, elastic parameters, and anisotropic damage were analyzed and investigated. The following results were obtained: (1) Acoustic-wave velocities of shale rocks are related to the confining pressure, soaking time, and coring angles. (2) Both Young's modulus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…Ma et al [21] proposed a novel theoretical method to underpin the failure mechanisms of anisotropic rocks under Brazilian test conditions. Gui et al [22,23] reported on anisotropic damage of shale stress coupled with hydration and proposed the conclusion that damage parameters parallel to bedding are greater than those perpendicular to bedding. Wan et al [24] analyzed the anisotropy of the diffusivity of gas shale, and the diffusivity is much higher at the parallel to the bedding direction than that at perpendicular direction.…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al [21] proposed a novel theoretical method to underpin the failure mechanisms of anisotropic rocks under Brazilian test conditions. Gui et al [22,23] reported on anisotropic damage of shale stress coupled with hydration and proposed the conclusion that damage parameters parallel to bedding are greater than those perpendicular to bedding. Wan et al [24] analyzed the anisotropy of the diffusivity of gas shale, and the diffusivity is much higher at the parallel to the bedding direction than that at perpendicular direction.…”
Section: Introductionmentioning
confidence: 99%
“…As for the hydration damage of shale oil reservoir and its influence on permeability, the following contents need to be supplemented. First of all, the existing research object of hydration damage is usually the outcrop core of marine strata [23,24]. Because of the difference of geological environment and lithologic composition, the research results cannot reflect the hydration damage law of continental oil shale reservoir.…”
Section: Introductionmentioning
confidence: 99%
“…Drilling fluid enters the wellbore through the action of hydraulic pressure difference and permeability potential difference. The rock around the wellbore is prone to hydration when it encounters water; hydration can reduce the rock strength and cause instability of the wellbore [6,22,23].…”
Section: The Circumferential Stress Generated By Ground Stress On Thementioning
confidence: 99%